Tinjauan Faktor Yang Mempengaruhi Waktu Tunggu Pelayanan Pendaftaran Pasien Rawat Jalan Di RS DKT Sidoarjo - Zein, Eiska Rohmania; Mujizah, Ahfil (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda (JIPIKI), 2024)
One form of administrative service at the hospital is the medical record service. The problem in the medical record installation at DKT Sidoarjo Hospital is the waiting time for outpatient medical record services. Based on Permenkes RI No.129/Menkes/SK/II/2008 for patient medical record services at outpatient registration, namely > 10 minutes. This study aims to determine the factors that influence the waiting time for medical record services at outpatient registration at DKT Sidoarjo Hospital. The research method is descriptive with instruments in the form of observations and interviews conducted with the head of medical records and medical records officers in the registration section. The results of this study indicate that the factor that greatly influences the waiting time for medical record services at TPPRJ DKT Sidoarjo Hospital is medical record activities, namely the provision of medical records in the storage section. On the Man Factor, namely the number of officers and educational qualifications of officers who are not from medical records. On the Money Factor there are no funds for the education and training of registration officers and no rewards for officers who are disciplined and friendly in service. In the Methode Factor the use of Registration SOP is not optimal. In Material Factors there is no use of tracers on storage racks. On the Machine Factor, namely frequent errors on SIMRS when performing services.